Essence of "Political Myth" - Khizanishvili, Salome (Advances in Social Sciences Research Journal, 2020)
In XIX-XX centuries, both origin of the new political myth and its subsequent development were linked to radical changes in the history of mankind. "The Death of God" is the most dangerous result caused by these changes. The "ungodly world" is dominated by historical people. In order to change reality, the growth of his creative ambitions increases the risk of his freedom. This reality is evident in Nietzsche’s doctrine, where nihilism achieves self-awareness and the will to power is declared to be "the meaning of great politics”. In modern analogies of political myth, the theme of the "apriority" of human freedom and the influence of the powerful person (nation, state) are getting more active. Their impact on human masses is quite big. What kind of positive and negative results can we obtain from such deep, comprehensive, and serious challenges? We can find the answers in the necessary conclusions on the topic in literary and philosophical works. At the turn of the XIX-XX centuries, Nietzsche’s doctrine gets our attention. With humanistic pathos, he endures time. He aims to solve the puzzles of eternal existence and for this reason he gives meaningful advice to historical man. We believe that in modern conditions of technological management of political myth, the paradigm of political myth created by Nietzsche is viable. With this idea we feel a kind of need to pay more attention to the predictions of the genius of the era.